Perforated Oculomotor Nerve After Endovascular Coiling: Complete Regeneration After Microsurgical Repair. Case Report - Menovsky, Tomas; Zijden, Thijs van der; Voormolen, Maurits; Os, Luc Van; Helsen, Gregory; Maas, A.; Parizel, Paul M. (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2013)
Background and Importance We describe a patient who developed complete right oculomotor nerve palsy after endovascular coiling for a ruptured posterior communicating artery aneurysm caused by migration of the coils outside the aneurysm.Clinical presentation A 50-year-old woman was admitted with an acute subarachnoid hemorrhage. She underwent, on the day of admission, endovascular coiling of a ruptured posterior communicating artery aneurysm. Four hours postcoiling, complete right oculomotor nerve palsy developed because of extrusion of the coils outside the aneurysm. The patient recovered completely after surgical exploration with removal of the migrated coils and microsurgical repair of the oculomotor nerve.Conclusion This report illustrates that oculomotor nerve palsy is a rare complication after coiling of a posterior communicating artery aneurysm, and it should serve as a reminder to encourage neurovascular teams to consider surgical exploration in cases of third nerve palsy after endovascular coiling.
Keywords: aneurysm surgery; endovascular coiling; perforation; oculomotor nerve; microsurgical repair; complication